Recent advances on syngas conversion targeting light olefins. (1st August 2022) - Zhao, Shangqing; Li, Haiwei; Wang, Bo; Yang, Xiaolong; Peng, Yanhua; Du, Hui; Zhang, Yan; Han, Dezhi; Li, Zhuo
Graphical abstract: Two routes for the direct synthesis of light olefins from syngas. Highlights: Recent advances on the direct synthesis of light olefins from syngas was reviewed. Co2 C nanoprisms showed superior C2 = -C4 = selectivity at mild reaction conditions. A landmark breakthrough was achieved by designing a novel OX-ZEO catalyst concept. The core-shell structured catalyst enhanced the C2 = -C4 = yield by inhibiting the WGS. Abstract: The direct synthesis of light olefins (C2 H4, C3 H6 and C4 H8 ) from syngas (a mixture of H2 and CO) could supply the extra resources of these platform building blocks for the subsequent production of various chemicals, which has attracted wide interest in recent years. The Fischer-Tropsch synthesis (FTS) has become a classic process for the syngas transformation since 1925. However, the products selectivity, especially for the light olefins, still remains a great challenge owing to the limitation of the Anderson-Schulz-Flory (ASF) distribution. The present review highlights the recent advances on the state-of-the-art catalyst development (from 2016 to 2021) for the direct conversion of syngas to light olefins with the selectivity far more than the theoretical limit of ASF model, including the Co2 C quadrangular nanoprisms, metal oxides and zeolite (OX-ZEO) bifunctional catalysts. The active components and catalytic performances of those high-efficient catalysts, in particular the selectivity of light olefins, were compared and discussed in detail. Moreover, the established relationships between catalytic performance and active sites provided insights for designing catalysts with superior selectivity of desired light olefins. Finally, a comprehensive conclusion on the advantages and disadvantages of each catalyst system and perspectives for further optimization of the catalyst compositions and structure were discussed.